Targeted hand hygiene audits and training: an effective tool for improvement in hand hygiene compliance - Chaurasia, Ankita; Bharti, Sujit; Bajpai, Vijeta; Mishra, Anwita; Sharma, Avinash Kumar; Singh, Ranjeet; Sarode, Rahul (International Journal Of Community Medicine And Public Health, 2024)
Background: Hand hygiene (HH) is the simplest, but most effective infection prevention and control measure. This study was aimed to determine HH compliance among health care workers (HCWs) in a cancer hospital and the impact of targeted and phased training over changes in HH compliance and determination of Hawthorne effect among HCWs. Methods: Prospective observational study conducted in two phases by HH trained auditor (Overt observer) and ICN (Covert observer) performing 30 minutes HH audit at ICU, haemato-lymphoid (HL) ward and paediatric ward to observe the pattern of HH compliance among HCW for HH moments and its impact over Hawthorne effect for HH compliance. Results: Highest compliance for HH was observed at HL ward (59.34%) in first phase and at ICU (70.08%) in second phase. Gradual and significant improvement in HH compliance was observed for ICU (52.24% to 70.08%), HL ward (59.34% to 68.48%) and paediatric ward (43.42% to 53.46%). Profession specific Hawthorne effect was observed for nurses with higher compliance in covert observation in first phase and for doctors with higher compliance in overt observation in second phase of the study. Conclusions: Regular targeted HH audit with motivational training is the better influential tool for improving HH compliance. Regular audits also improve efficiency of auditor for effective HH compliance supervision. Decentralization and availability of workstation specific HH auditor is the most of effective cost saving approach for achieving significant progressive improvement in HH adherence.